Preparation and In Vitro Evaluation of Monoquaternary Inhibitors of Brain Cholinesterases - Jun, Daniel; Paar, Martin; Binder, Jiri; Marek, Jan; Pohanka, Miroslav; Stodulka, Petr; Kuca, Kamil (Letters in Organic Chemistry, 2009)
Acetylcholinesterase inhibitors are currently of high interest due to the many reasons. Among them, Alzheimer's disease drugs are of great interest. In this study, eleven monoquaternary pyridinium salts substituted by different groups (electron donors and electron acceptors) in position four were prepared. Then, their anticholinesterase activity was tested. As observed, their IC50s ranged from 33 μM to 3981 μM. Moreover, probability of blood-brain barrier penetration was predicted.
Keywords: pyridinium salts